Chemical elements in the water of the São Pedro river basin, Faxinal - Paraná - Justus, Cláudia Maria; Pasini, Amarildo; Raminelli, Jaqueline Aparecida; Gonçalves, Leandro Simões Azeredo; Celligoi, André (Semina: Ciências Agrárias, 2020)
Anthropogenic activities close to water bodies can be sources of contamination, posing a risk to the environment and human health. This study aimed to assess the chemical composition of surface and groundwater samples collected from the São Pedro river basin, in the municipality of Faxinal (PR-Brazil). Thirty-eight samples were collected in total: nineteen from rivers, two in dams, eleven at sites with springs, one in a shallow well, and five in deep wells part of the Guarani Aquifer System. Samples were collected in the rainy and dry seasons to determine the concentrations of the following elements: Magnesium, Copper, Manganese, Zinc, Chromium, Nickel, Aluminum, Lead, Mercury, and Cadmium, which were quantified using atomic absorption spectrometry (AAS) and atomic emission spectrometry (ICP-MS). The results were compared with the standards established by the Brazilian Ministry of Health Ordinance n. 2914/2011, which regulates the drinking water standard for human consumption in Brazil. Manganese, Aluminum, and Mercury levels were observed to be above those required by the standards established by the legislation, indicating that further studies are necessary to detect possible sources of pollution in these waters as well as highlighting the potential risks to human health and ultimately contributing to the environmental planning of this basin.